Bernard Malamud papers - Malamud, Bernard
Part I includes correspondence, memoranda, manuscripts, notes, legal and financial papers, printed material, and other papers relating primarily to Malamud's writings. Includes complete files of drafts, notes, and outlines for each of his novels and volumes of short stories as well as for many of his other works of short fiction. The collection documents his dealings with editors, literary agents, and publishers, his work on theatrical and motion picture adaptations of his writings, his defense of free speech as president of the American Center of P.E.N. (1979-1981), and his support of the artistic community while on the board of directors of the American Academy and Institute of Arts and Letters. Correspondents include literary agents in the firm of Russell and Volkening and staff of the publishing firm of Farrar, Straus, and Giroux.
Papers in Part II supplement the topics and files in Part I and also include notes and outlines for classroom lectures given by Malamud at Bennington College, Bennington, Vt., and drafts and notes for public lectures and readings.
Library of Congress Motion Picture, Broadcasting and Recorded Sound Division.
Author. Born 1914, died 1986.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: American Academy and Institute of Arts and Letters; American Center of P.E.N.; Bennington College -- Faculty; Farrar, Straus & Giroux; Russell and Volkening; American literature; Freedom of speech; Universities and colleges -- Vermont -- Bennington; Artists -- United States; Authors